A rapid method for the assay of methylxanthines alkaloids: Theobromine, theophylline and caffeine, in cocoa products and drugs by paper spray tandem mass spectrometry. (25th April 2019) - Bartella, Lucia; Di Donna, Leonardo; Napoli, Anna; Siciliano, Carlo; Sindona, Giovanni; Mazzotti, Fabio
Highlights: Quantitative determination of methylxanthines alkaloids in cocoa products. Paper Spray mass spectrometry for analytical assay. Comparison of obtained data with HPLC/UV method. Abstract: A fast method for the determination of methylxanthines in cocoa products and drugs based on PS-MS/MS under MRM condition has been developed. Analyte ions were generated by applying a high voltage on a paper substrate drenched of sample extract using a small volume (∼15 μL) of spray solvent. The gas phase chemistry of the molecules under investigation has been elucidated. The accuracy values of the methodology ranged from 95 to 110%, while the analytical parameters LOQ, LOD, recovery and reproducibility, calculated analyzing spiked samples, confirmed the consistency of the proposed method. Furthermore, real samples have been analyzed both by the developed methodology and by using a classical HPLC-UV approach obtaining comparable values.